O entrelaçar coesivo e a variação lingüística: um percurso didático-metodológico à luz da linguística textual - Valle, Carmen Lúcia Bueno (2009)
Based on the theoretical presuppositions of Textual Linguistics and grounded on postulates of the varied Socio-Linguistics, this research wishes to cause a reflection on the possibility of approximation between theory and practice, from verifying the results obtained from texts written by first-year high school students, diastratic linguistic variation users, by means of teaching strategies on text study, in its macro and micro structures. The purpose of this paper is to show that one of the possible ways leading to an effective practice of the Portuguese language teaching, especially in a context of linguistic variation, like the one presented by this alumni group, may be constructed by the teaching of Textual Linguistics, with the aim of making students become textually competent. Through the study of linguistic theories, the analysis was carried through students textual productions in two distinct periods: from the results of the application tests for the selection of applicants and a textual production done by the end of the year with high school students. In both occasions, the writing proposed to students was the same, the creation of a letter to a school newspaper. The comparative analysis between initial and final texts demonstrates a considerable progress in the linguistic competence and register, composed by the accuracy of correct spelling, the use of a wide variety of lexis, and mainly in the cohesion of the produced texts, which was the focus of this research, providing a valuable contribution to the meaning of the text, the coherence. The presentation of a standard pattern of writing was focused, and also a variant one to be used in certain situations, regarding the non-standard writing brought by students as an identity element to their socio-cultural universe. It was concluded that the students proper register and linguistic progress, mainly textual related progress, are possible by means of translating the Textual Linguistics into the practice of Portuguese Language Teaching.